SIRT4 and Its Roles in Energy and Redox Metabolism in Health, Disease and During Exercise - Han, Yumei; Zhou, Shi; Coetzee, Sonja; Chen, Anping (Frontiers in Physiology, 2019)
NAD+-dependent SIRT4 has been reported to be a key regulator of metabolic enzymes and antioxidant defense mechanisms in mitochondria. It also plays an important role in regulation of mitochondrial metabolism in response to exercise. Recent studies have shown that SIRT4 is involved in a wide range of mitochondrial metabolic processes, including depressing insulin secretion in pancreatic beta cells, promoting lipid synthesis, regulating mitochondrial adenosine triphosphate (ATP) homeostasis, controlling apoptosis and regulating redox. SIRT4 also appears to have enzymatic functions involved in posttranslational modifications such as ADP-ribosylation, lysine deacetylation and lipoamidation. However, the effects on SIRT4 by metabolic diseases and changes in metabolic homeostasis such as during exercise, along with the roles of SIRT4 in the regulation of metabolism during disease, are not well understood. The main goal of this review is to critically analyse and summarise the current research evidence on the significance of the SIRT4 as a metabolic regulator and in mitochondrial function and its putative roles in relation to metabolic diseases and exercise.